If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2cos(x) + 1 = 0.5 Multiply cos * x 2cosx + 1 = 0.5 Reorder the terms: 1 + 2cosx = 0.5 Solving 1 + 2cosx = 0.5 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 2cosx = 0.5 + -1 Combine like terms: 1 + -1 = 0 0 + 2cosx = 0.5 + -1 2cosx = 0.5 + -1 Combine like terms: 0.5 + -1 = -0.5 2cosx = -0.5 Divide each side by '2osx'. c = -0.25o-1s-1x-1 Simplifying c = -0.25o-1s-1x-1
| 5x^2+28x+-12=0 | | 6+6x=-60 | | 1.25g=15g+.50 | | y=2(1)+2.50(1) | | -4+7x=-46 | | 4+8=8+x | | 12x^2+-8x+1=0 | | n+6.92=11.77 | | -7-3x=29 | | 14.75g=.50 | | (2x+10)(3x-1)=150 | | 3p+45=68 | | 1.5-2= | | (5w-1)(5+w)=0 | | (2x-3)+1=17 | | 3.5+-9= | | -3(1-4n)=-63 | | y=2*4+2.50*4 | | (7+4w)=13 | | -26+7p=5(3p+6) | | -3(1-4n)=63 | | -3(1-4)=-63 | | 1.5-7= | | y=2(2)+2.50(2) | | 3b+-4=14 | | -15a-a+4=64 | | -21n-15=-82 | | -13a-18=73 | | 21x-28= | | h=-16t^2+16t+112 | | -3(x-1)+8(x-3)=6x-5x | | -5k-7=-37 |